Ecotourism potential in Protected Natural Areas. Case: Tirimbina Biological Reserve (RBT), Sarapiquí, Province of Heredia, Costa Rica. - Arroyo-Solórzano, Mario; Rojas-Prendas, Lincenth (Revista Geográfica de América Central., 2021)
This article describes the main tourism potentials of the Reserva Biológica Tirimbina (RBT) (translated as Tirimbina Biological Reserve).  The ecotourism potential level is determined based on an analysis of important variables and from the descriptive characteristics of RBT.  Currently, RBT sustains multiple nature and educational research programs, as well as a striking offering of tours that promote tourist interaction and learning in nature-based settings.  According to the proposed weighting methodology, where six relevant variables were identified and each variable evaluated based on key attributes assigned individual corresponding weight values, RBT is characterized as possessing a high ecotourism potential wherein ecological trail hiking activities predominates over all evaluated attributes.  The reserve is a source of employment for the local population, promotes environmental protection and education, and greatly boosts tourism with the potential to link to other more consolidated touristic value chains.